Faktor-Faktor Yang Mempengaruhi Motivasi Belajar Daring Pada Mahasiswa Keperawatan S1 Di Masa Pandemi COVID-19 Universitas Muhammadiyah Purwokerto - Riska Apriana Saputri; Etlidawati Etlidawati (Jurnal Keperawatan Muhammadiyah, 2021)
Objective : To find out the factors that affected the motivation on online learning in undergraduate nursing students of Universitas Muhammadiyah Purwokerto during the Covid-19 pandemic.Methods: The study used a quantitative research method with a cross-sectional design. The sampling technique was a proportional stratified random sampling technique with a sample of 88 respondents who met the inclusion and exclusion criteria.Results: The results revealed that there were 70 respondents (79.5%) who were 20 years old. There were 35 respondents (39.8%) who were in the fifth semester. The results of the chi-square test showed that the p values on the variables of interest, ability, and learning environment were 0.001; 0.08; and 0.029Conclusion: there is a correlation between students’ interest and learning environment with motivation on online learning for undergraduate nursing students during the Covid-19 pandemic. There is no correlation between students’ ability and motivation on online learning for undergraduate nursing students during the Covid-19 pandemic.